Environmental Milestones and Ecosystem Services and Economic Origins - Mirici, Merve Ersoy (KARE PUBL, 2021)
Increasing population and industrial developments in the last century have caused dramatic effects on ecosystem functions. The fact that the ecosystem resources of the world are limited and the increasing supply and demand for these resources have revealed that natural resources should be investigated in more detail. In this direction, ecosystem good and services have turned into a research field that has been increasing gradually for the last ten years as a landscape, urban and region planning tool. There are many differences and complexities in the system of definition, scope and categories of ecosystem services. In addition to the diversity of definition and categorization, the ecological outputs of ecosystem products and services cannot be transformed into an economic basis. In this case, the ecosystem services studies exhibit an approach that is handle within a narrow scope. This study focuses on ecosystem services from a superficial point of view, rather than nature and indirectly the position of the ecosystem within human-environmental thinking systems. One of the most important driving forces determining this position is the economy. The ecosystem services approach has been shaped by many environmental movements and actions that have taken place in the past rather than being a newly discovered concept. In this context, this study has been carried out to contribute to the lack of literature in the interface of ecological and economic interference with the transformations of ecosystem good and services, changing perspectives, key persons and key events.
Keywords: Environmental viewpoint; ecological economics; economic origin; ecosystem good and services; landscape